No effect of repeated post-resistance exercise cold or hot water immersion on in-season body composition and performance responses in academy rugby players: a randomised controlled cross-over design - Horgan, B. G.; Halson, S. L.; Drinkwater, E. J.; West, N. P.; Tee, N.; Alcock, R. D.; Chapman, D. W.; Haff, G. G. (European Journal of Applied Physiology, 2023)
Purpose Following resistance exercise, uncertainty exists as to whether the regular application of cold water immersion attenuates lean muscle mass increases in athletes. The effects of repeated post-resistance exercise cold versus hot water immersion on body composition and neuromuscular jump performance responses in athletes were investigated.